Peran Guru dalam Menghadapi Tantangan Pengembangan Kurikulum Pendidikan Agama Islam di Abad 21 di Sekolah MA Al-Amin Bogor, SMPIT Roudlotul Jannah Ciawi, dan SDIT Darul Ma’arif - Herliawati, Lia; Kartika, Ika; Yulistiani, Siti Alfiah; Humairo, Shovi Sholahiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The rapid development of the era demands Islamic religious education to continuously adapt. Increasing students' literacy is a major challenge in developing the Islamic Religious Education (PAI) curriculum in the digital era. The Merdeka Curriculum provides schools with more flexibility in designing learning that is suitable for students' characteristics. This study aims to examine the role of teachers in facing the challenges of developing the Islamic Religious Education curriculum in the 21st century, especially at MA Al-Amin Bogor, SMP IT Roudlotul Jannah Ciawi, and SDIT Darul Ma'arif. The method used in this research is a qualitative field research method, which is a field study by examining a case. Data was collected through in-depth interviews, observations, and document studies of research respondents. Data analysis was carried out in stages, namely data collection, data reduction, conclusion, and verification. The results of the study show that the role of teachers is very important in facing the challenges of developing the Islamic Religious Education curriculum in the 21st century, at MA Al-Amin Bogor, SMP IT Roudlotul Jannah Ciawi, and SDIT Darul Ma'arif. Through teaching experience, the author analyzes the required teacher competencies, efforts to adapt to changing times, and learning innovations that can be carried out. A case study of problem-based learning in the Islamic History and Culture (SKI) subject with the utilization of blogs as a learning medium, as well as the development of digital-based teaching materials using Canva and CapCut, will be the focus of the discussion. The challenges faced, innovations made, and their impact on student learning will be discussed in depth.